2021
DOI: 10.1186/s12978-021-01218-4
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of family, community and religious leaders and acceptability for minimal invasive tissue sampling to identify the cause of death in under-five deaths and stillbirths in North India: a qualitative study

Abstract: Background Minimal invasive tissue sampling (MITS) has emerged as a suitable alternative to complete diagnostic autopsy (CDA) for determination of the cause of death (CoD), due to feasibility and acceptability issues. A formative research was conducted to document the perceptions of parents, community and religious leaders on acceptability of MITS. Methods This qualitative study was conducted at and around the Safdarjung Hospital, Delhi, India. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…One notable exception was that single mothers were more likely to consent to MITS independently or with only female family members present, possibly explained by the matrilocal setting 20. In cases where the father was at least somewhat involved, they were engaged in the consent process and often had the principal authority to consent, corroborating hypothetical findings from formative MITS acceptability research in Mozambique, South Africa, Bangladesh, India and Pakistan 6 8 9 21 22. Interestingly, relationships with HCWs or research staff (neither positive nor negative) or dissatisfaction with the healthcare provided, did not seem to strongly influence decision-making among MiM participants, even though many did report negative interactions.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…One notable exception was that single mothers were more likely to consent to MITS independently or with only female family members present, possibly explained by the matrilocal setting 20. In cases where the father was at least somewhat involved, they were engaged in the consent process and often had the principal authority to consent, corroborating hypothetical findings from formative MITS acceptability research in Mozambique, South Africa, Bangladesh, India and Pakistan 6 8 9 21 22. Interestingly, relationships with HCWs or research staff (neither positive nor negative) or dissatisfaction with the healthcare provided, did not seem to strongly influence decision-making among MiM participants, even though many did report negative interactions.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, relationships with HCWs or research staff (neither positive nor negative) or dissatisfaction with the healthcare provided, did not seem to strongly influence decision-making among MiM participants, even though many did report negative interactions. This is in contrast to qualitative work pre-MiM study implementation from our group and other formative studies that suggested trust in the healthcare system and relationships with HCWs and research staff would be important drivers of consent 14 21. However, the data from our in-depth interviews are only among those who consented to MITS and reflect families’ experiences 6 weeks after the death and MITS procedure 4 5 14.…”
Section: Discussionmentioning
confidence: 70%
“…Proper counselling of the parents and family, based on sociocultural and religious grounds along with the good care, behaviour and empathetic conversation by the healthcare providers can improve acceptability of MITS[ 30 ]. Above descriptive findings are not anecdotal.…”
Section: Discussionmentioning
confidence: 99%
“…Our team got permission from independent ethical committee and health ministry screening committee of government of India for all of the procedures mentioned in the manuscript. Proper counselling of the parents and family, based on sociocultural and religious grounds along with the good care, behaviour and empathetic conversation by the healthcare providers can improve acceptability of MITS [ 30 ]. To know surely the cause of death (CoD) to guard their upcoming children was the key incentive for participation and consenting by parents in MITS.…”
Section: Discussionmentioning
confidence: 99%
“…As such, in talking to parents or obtaining consent for an autopsy, it is necessary to bear this in mind and inform them about the different types of autopsies available. The uptake of PM has increased significantly amongst these religious groups in HMICs since the introduction of MITS and non-invasive autopsy ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%